Effect of laser therapy on the treatment of pressure injuries in adult patients: integrative review (Research, Society and Development, 2020)
Pressure injuries are characterized by skin damage resulting from intense or prolonged pressure. Brazil has high incidence rates of pressure injuries in hospitalized patients, which makes laser therapy an alternative adjuvant treatment for tissue repair. The present study aimed to analyze the effectiveness of low-power laser therapy in the treatment of pressure injuries in adult patients. This is an integrative review with eight articles selected from the Lilacs, Pubmed and Medline databases between 2010 and 2020. After reading, analyzing and interpreting the data, it can be seen that, despite there are few recent studies on laser therapy on the subject of pressure injuries, the articles elucidate the use of laser as a promising treatment modality, which reduces the healing time and improves the appearance of wounds. However, the studies present different application parameters, wavelengths, energy density and treatment frequency, which makes it impossible for the authors to agree on the laser application technique. There is a need for further research to create and elucidate standards or protocols in order to optimize the quality of care for patients with pressure injuries and promote the dissemination of laser therapy as a safe and effective treatment.